2006
DOI: 10.1103/physrevd.74.054027
|View full text |Cite
|
Sign up to set email alerts
|

Dual parametrization of the proton generalized parton distribution functionsHandE, and description of the deeply virtual Compton scattering cross sections and asymmetries

Abstract: We develop the minimal model of a new leading order parameterization of GPDs introduced by Shuvaev and Polyakov. The model for GPDs H and E is formulated in terms of the forward quark distributions, the Gegenbauer moments of the D-term and the forward limit of the GPD E.The model is designed primarely for small and medium-size values of x B , x B ≤ 0.2. We examined two different models of the t-dependence of the GPDs: The factorized exponential model and the non-factorized Regge-motivated model. Using our mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(127 citation statements)
references
References 56 publications
2
123
2
Order By: Relevance
“…We have also found in the expansion with respect to Legendre polynomials, which was used in Ref. [91], that the minimal version of the dual model, i.e., taking leading and next-to-leading partial waves, yields also an astonishing agreement with the exact result. We have also observed that in the experimentally accessible kinematical region the expansion in ξ practically coincides with the exact result, in particular for the imaginary part.…”
Section: Modelling Of Conformal Gpd Momentssupporting
confidence: 58%
See 3 more Smart Citations
“…We have also found in the expansion with respect to Legendre polynomials, which was used in Ref. [91], that the minimal version of the dual model, i.e., taking leading and next-to-leading partial waves, yields also an astonishing agreement with the exact result. We have also observed that in the experimentally accessible kinematical region the expansion in ξ practically coincides with the exact result, in particular for the imaginary part.…”
Section: Modelling Of Conformal Gpd Momentssupporting
confidence: 58%
“…After crossing, cos θ becomes 16 the inverse of the scaling variable −η, i.e., cos θ = −1/η [24,90]. The basis of Legendre polynomials has later been adopted for the conformal moments of nucleon GPDs, too [91]. Let us here start with the analysis and discussion which basis of polynomials one should employ.…”
Section: So(3) Partial Wave Decomposition Of Conformal Gpd Momentsmentioning
confidence: 99%
See 2 more Smart Citations
“…By the decomposition into Mellin moments it is straightforward to perform QCD evolution in this model. Calculations have been done by Guzey and Teckentrup [7]. Their dual parameterization with the Regge motivated t-dependence were used as model 3 in the simulations for COMPASS.…”
Section: Simulationsmentioning
confidence: 99%